ORGANOGÊNESE INDIRETA A PARTIR DE EXPLANTES FOLIARES E MULTIPLICAÇÃO IN VITRO DE BROTAÇÕES DE Eucalyptus benthamii X Eucalyptus dunnii - Yohana de Oliveira-Cauduro; Laís Gomes Adamuchio; Juliana Degenhardt-Goldbach; João Carlos Bespalhok Filho; Roberson Dibax; Marguerite Quoirin (Ciência Florestal, 2014)
The aims of this research were to evaluate different culture media for indirect organogenesis and shoot multiplication of Eucalyptus benthamii x Eucalyptus dunnii . For organogenesis, leaf explants were used to test the following treatments: two culture media (MS N/2 and JADS) supplemented with 0.1 μM 1-naphthaleneacetic acid (NAA) and thidiazuron (TDZ) (0.1 or 0.5 μ M), with or without PVP- 40 (250 mg L -1 ). The percentage of oxidized explants, callus forming explants, explants with anthocyanin,buds, shoots and the shoot number per explant were evaluated. In the multiplication experiment, isolated shoots were cultivated in MS, JADS and WPM media, all supplemented with 1.11 μ M BAP. Four subcultures were carried out every 28 days. In every subculture the explant oxidation, partial or total leaf chlorosis, fresh mass and mean number of shoot per explant were evaluated. The MS N/2 medium supplemented with 0.1 μM NAA and 0.5 μM TDZ promoted the highest rate of organogenesis (8.3%) and the culture media MS supplemented with 1.11 μ M BAP the multiplication rate was higher than in the other media, in the first and the second subcultures (9.28 and 9.24, respectively), without differences between the three media in the following subcultures.